Application of the Snowball Throwing Model in Improving Skills Writing Review Texts at Makassar City Middle School - Supriadi, Supriadi; Tasya, Tasya; Erniati, Erniati (Lembaga Sembilan Tiga Community, 2024)
This research aims to determine the application of the snowball throwing model to improve review text writing skills in Makassar City Middle School students. The type of research used is Classroom Action Research. The research was carried out over 2 cycles. Each cycle consists of planning, implementation, observation and reflection. The subjects studied were 31 students in class VIII of SMP Negeri 34 Makassar , consisting of 16 male students and 15 female students . Data collection was carried out using observation and tests. The instruments used consisted of learning implementation observation sheets and review text writing skills tests . The data analysis used is descriptive data analysis . The results of the research show that the application of the S nowball T hrowing model is able to improve the review text writing skills of junior high school students in Makassar City . This was obtained based on data obtained from the results of research on the learning process which was carried out in two cycles. Data on the ability to write review texts was obtained. The data obtained were that 26 students (83.9%) had obtained a complete score and 5 students (16.1%). Based on the success indicators applied at school, it is said to be complete if the number of students ≥ 75% of students get a score of 75 or above .